Influence of timing of postexercise carbohydrate-protein ingestion on selected immune indices - Costa, R. J. S.; Oliver, S. J.; Laing, S. J.; Walters, R.; Bilzon, J. L. J.; Walsh, N. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
The aim of the study was to determine the influence of immediate and 1-hr-delayed carbohydrate (CHO) and protein (PRO) feeding after prolonged exercise on leukocyte trafficking, bacterially stimulated neutrophil degranulation, saliva secretory IgA (S-IgA) responses, and circulating stress hormones. In randomized order, separated by 1 wk, 9 male runners completed 3 feeding interventions after 2 hr of running at 75% VO2max. During control (CON), participants received water (12 ml/kg body mass [BM]) immediately and 1 hr postexercise. During immediate feeding (IF), participants received a CHO-PRO solution equal to 1.2 g CHO/kg BM and 0.4 g PRO/kg BM immediately postexercise and water 1 hr postexercise. During delayed feeding (DF), participants received water immediately postexercise and CHO-PRO solution 1 hr postexercise. Unstimulated saliva and venous blood samples were collected preexercise, immediately postexercise, and every 20 min until 140 min postexercise. No significant interactions were observed for circulating leukocytes and T-lymphocyte subset counts, S-IgA secretion rate, or plasma cortisol, epinephrine, or norepinephrine concentration. Bacterially stimulated neutrophil degranulation decreased during recovery on CON and DF (24% and 31%, respectively, at 140 min; p < .01) but not on IF. Compared with CON, neutrophil degranulation was higher on IF at 100 min postexercise and higher on IF than DF at 80 min and 100 min onward postexercise (p < .05). Ingestion of a CHO-PRO solution immediately after, but not 1 hr after, prolonged strenuous exercise prevented the decrease in neutrophil degranulation but did not alter circulating stress hormone, leukocyte trafficking, or S-IgA responses. Further research should identify the independent effect of different quantities of CHO and PRO ingestion during recovery on neutrophil responses and other aspects of immune function.